The moderating effect of shareholder features on dividend disbursement: evidence from Indonesia - Novi Swandari Budiarso; Winston Pontoh (Investment Management & Financial Innovations, 2018)
The objective of this study is to give an empirical evidence of relationship between features of ownership structures and dividend disbursement in context of bird in the hand and catering theories. The study uses 241 listed firms as the sample, which were drawn from Indonesia Stock Exchange during the period from 2010 to 2015. Under condition that dividend policy is not moderated by ownership features, dividend policy for firms with multi-institutional, single institutional, and state are fit in context of bird in the hand theory and catering theory. Under condition that dividend policy is moderated by ownership features, this study finds that dividend policy for firms with state ownership is not fit both in context of bird in the hand theory and catering theory. Specifically, the study finds that firms with features of: (1) multi-institutional, single individual, and public; (2) multi-institutional, multi-individual, and public; and (3) single institutional, and public are fit with bird in the hand theory. Furthermore, this study finds that catering theory is not fit for firms with basic features of multi-institutional and state ownership, but it is fit for firms with features of single institutional, single individual, and public ownership.